HARMONIZATION OF EUROPEAN LEGISLATION IN THE FIELD OF SAFETY AND HEALTH AT WORK IN THE LEGAL SYSTEM OF THE REPUBLIC OF NORTH MACEDONIA - Majhosev, Andon; Jovanov, Kristijan (Journal of process management and new technologies, 2021)
Occupational safety and health is one of the most important international labor standards of ILO. This means that ILO member states should ensure encouraging and maintenance at the highest level of safe working conditions in order to avoid accidents and occupational diseases. Achieving this goal means that employers must make a continuous risk assessment at the workplace, and at the same time decide whether appropriate measures and activities are necessary in order to create the highest level of safety and health at work, i.e. to avoid side effects. In order to achieve this goal, a systematic approach is necessary in preventive action and connection of all entities that are bearers of certain obligations and activities at the national level, but also beyond the international institutions in this area. By application for membership of the Republic of Macedonia in the European Union on 22 of March 2004, the process of harmonization of the domestic with the European labor legislation begins, and thus inevitably harmonization of the domestic legislation for safety and health at work with the European. Thereby, this process takes place pursuant to article 32 of the Constitution of the Republic of Macedonia, according to which the protection of workers is of primary importance, i.e. health and safety at work is a constitutional-legal category and every individual has the right to work, free choice of employment and work protection. In the harmonization process the basic concept is the Framework Directive 389/391/EES for safety and health at work, according to which the national legislation on safety and health at work should be harmonized exactly according to the principles of this directive.